Exclusion of Minority Group through Structural Violence: A Case Study of Rohingya - Ali, Nadia Zaheer; Binyameen, Muhammad Ali (Annals of Human and Social Sciences, 2023)
In Myanmar, a minority community of Muslim Rohingya has been systematically facing the persecution for many years. Following the Ne’s Win regime in Myanmar and implementation of the Citizenship Act of 1982, the Rohingya Muslim community experienced social, cultural, and political hardships. Buddhists, the majority group disseminated state-level propaganda against the Rohingya community which resulted in the 1982 Citizenship Act, which essentially institutionalized the violation of the rights of the Rohingya Muslims in Myanmar, and therefore continued the structural violence. Despite the gravity of the problem, Myanmar rejects any notion that the government is an oppressor and this refusal to acknowledge the problem has resulted in multi-dimensional conflicts. The Rohingya Muslim population is fleeing to neighboring countries in search of safe sanctuaries, leading to the greatest refugee catastrophe in Asia. Therefore, this descriptive research adopts case study method while using theoretical framework of structural violence to understand the exclusion of Rohingya Muslims in their country and also highlights the implication of refugee crisis for regional politics.